IMPACT OF RURAL COMMERCIAL CENTRES ON RURAL DEVELOPMENT IN COOCHBEHAR DISTRICT, WESTBENGAL - DR. RATAN CHANDRA PAUL (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2026)
Rural market has acquired significance as the overall growth of the country economy. Due to agriculture sector development, has resulted into substantial increase in the purchasing capability of the rural communities. At Present rural people are consuming a large quantity of industrial; FMCG (Faster Moving Consumers Goods) and agricultural manufacturing goods. In this reason rural market centers have been emerging very fast. The rural market of India has been growing at 12-13% comparing to the 7-8% growth of its urban counterpart. In recent years, rural market centers have become more modernized. The growth of rural income, growing population, improving rural infrastructures and numbers of favourable Govt. Development policies offer huge potentiality for rural market centers development which one can’t ignore. Growth in agriculture has resulted in the rapid rise of rural income. The increased income causes a spurt in the demand for consumers’ non-durable and durable products. Due to huge demands of industrial product in rural area, rural market centers became small to big after 1990.